A Bayesian control chart for monitoring the ratio of Weibull percentiles. (18th July 2019) - Erto, Pasquale; Lepore, Antonio; Palumbo, Biagio; Vanacore, Amalia
Abstract: This paper introduces a new Bayesian control chart to compare two processes by monitoring the ratio of percentiles of two quality characteristics that are assumed to be independent Weibull distributed random variables with the same and stable shape parameter larger than one. The chart analyses the sampling data directly, instead of transforming them in order to comply with the usual normality assumption, as many charts do. A real application in the wood industry and a wide simulation illustrate the features of the chart and its performance, depending on the number of training data, the quality of prior information, and the magnitude of the shift.